2013
DOI: 10.1148/radiol.12120010
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Cognitive Decline in Subjects at Risk for Alzheimer Disease by Using Combined Cerebrospinal Fluid, MR Imaging, and PET Biomarkers

Abstract: For the Alzheimer's Disease Neuroimaging InitiativePurpose:To assess the extent to which multiple Alzheimer disease (AD) biomarkers improve the ability to predict future decline in subjects with mild cognitive impairment (MCI) compared with predictions based on clinical parameters alone. Materials and Methods:All protocols were approved by the institutional review board at each site, and written informed consent was obtained from all subjects. The study was HIPAA compliant. Alzheimer's Disease Neuroimaging Ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
182
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(200 citation statements)
references
References 41 publications
13
182
0
5
Order By: Relevance
“…This is in line with published evidence, e.g. the assessment of a panel of biomarkers combined instead of a biomarker alone (whatever it is) drastically increases the diagnostic accuracy in MCI and AD patients [7][8][9][10]24,43].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is in line with published evidence, e.g. the assessment of a panel of biomarkers combined instead of a biomarker alone (whatever it is) drastically increases the diagnostic accuracy in MCI and AD patients [7][8][9][10]24,43].…”
Section: Discussionsupporting
confidence: 90%
“…Some structured programs are currently ongoing where MCI patients are assessed by traditional clinical assessment supported by an extended range of core biomarkers that include MTA, CSFAb/tau, and hypometabolism on FDG-PET [7][8][9][10]. However, these programs are constrained to a limited number of academic memory clinics, whereas the measurement of individual biomarkers are now available to and used by a much larger number of memory clinics with a clinical research background, including those of the European Alzheimer's Disease Consortium (EADC, http://www.eadc.…”
Section: Introductionmentioning
confidence: 99%
“…For our predictive study, we utilized the dataset from an earlier study by Shaffer et al [52] based on ADNI-1. That particular study identified 97 MCI patients and predicted progression to AD dementia based on their clinical parameters, MRI results, PET scans, cerebrospinal fluid (CSF) markers (tau, p-tau181P, and β-amyloid1-42), the APOE ε4 genotype, and results from at least one follow-up clinical examination.…”
Section: Il-1βmentioning
confidence: 99%
“…Since the complexity of this scenario impairs the use of current diagnostic tools for a correct data interpretation, in the recent years, new strategies such as the integrated and combined use of neuropsychological profiles, imaging and biological fluids biomarkers have been developed, improving current diagnosis classification [9][10][11] and predicting the conversion from MCI to AD [12,13].…”
Section: Introductionmentioning
confidence: 99%